2015
DOI: 10.1007/s00709-015-0916-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of aquaporin function in mediating stomatal aperture gating among drought-tolerant and sensitive varieties of rice (Oryza sativa L.)

Abstract: Climate change drastically affects the cultivation of rice, and its production is affected significantly by water stress. Adaptation of a plant to water deficit conditions is orchestrated by efficient water uptake and a stringently regulated water loss. Transpiration remains the major means of water loss from plants and is mediated by microscopic pores called stomata. Stomatal aperture gating is facilitated by ion channels and aquaporins (AQPs) which regulate the turgidity of the guard cells. In a similar mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…However, AM regulation of aquaporins in the drought-tolerant genotype was weaker, and only three aquaporins ( ZmPIP1;6, ZmPIP2;2 , and ZmTIP4;1 ) were found to be altered. It is noteworthy that these three aquaporins were even up-regulated under well-watered conditions, which is an opposite behavior than in the sensitive genotype, similar to results reported by Liu et al (2013) or Vinnakota et al (2016) in two rice varieties and two Malus species with contrasting drought sensitivity. Also, upland rice and lowland rice with different responses to drought were compared to study the role of aquaporins in drought resistance and authors found important differences in PIP aquaporin transcriptional regulation in both types of rice (Lian et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, AM regulation of aquaporins in the drought-tolerant genotype was weaker, and only three aquaporins ( ZmPIP1;6, ZmPIP2;2 , and ZmTIP4;1 ) were found to be altered. It is noteworthy that these three aquaporins were even up-regulated under well-watered conditions, which is an opposite behavior than in the sensitive genotype, similar to results reported by Liu et al (2013) or Vinnakota et al (2016) in two rice varieties and two Malus species with contrasting drought sensitivity. Also, upland rice and lowland rice with different responses to drought were compared to study the role of aquaporins in drought resistance and authors found important differences in PIP aquaporin transcriptional regulation in both types of rice (Lian et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…During drought stress episodes, water conservation is critical for plant survival and productivity, and is achieved by an efficient uptake and stringently regulated water loss, in which aquaporins participate (Vinnakota et al, 2016). Our results in the drought-sensitive cultivar are in line with the hypothesis that down-regulation of aquaporins under water deprivation could be a way to minimize water loss, and the AM symbiosis could be helping the plant in this regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, ZmPIP1s and ZmPIP2s are also strongly expressed in roots, indicating that these aquaporins are involved in connecting water uptake in the rhizosphere with leaf evapotranspiration. Furthermore, GC protoplasts from two drought‐tolerant rice varieties (Anna and DBN) had higher osmotic water permeability coefficients compared with a drought‐sensitive variety (ADT‐39), while in roots this trend seemed to be inverted (albeit not significantly; Vinnakota et al , ). Despite the difference in the GCs osmotic permeability no significant differences were found in the expression patterns of PIPs (PIP1 and PIP2) for ADT‐39 and Anna, while the drought‐tolerant variety (DBN) presented an increased expression of OsPIP1;1 , OsPIP1;2 , OsPIP2;1 , OsPIP2;4 and OsPIP2;5 (Vinnakota et al , ).…”
Section: Better Faster More Efficient – How An Innovative Morphologmentioning
confidence: 98%
“…Furthermore, GC protoplasts from two drought‐tolerant rice varieties (Anna and DBN) had higher osmotic water permeability coefficients compared with a drought‐sensitive variety (ADT‐39), while in roots this trend seemed to be inverted (albeit not significantly; Vinnakota et al , ). Despite the difference in the GCs osmotic permeability no significant differences were found in the expression patterns of PIPs (PIP1 and PIP2) for ADT‐39 and Anna, while the drought‐tolerant variety (DBN) presented an increased expression of OsPIP1;1 , OsPIP1;2 , OsPIP2;1 , OsPIP2;4 and OsPIP2;5 (Vinnakota et al , ). The change in water permeability despite equivalent expression of aquaporins in GCs may indicate a less efficient gating capacity in the drought‐sensitive variety and thus slower stomatal aperture control (Vinnakota et al , ).…”
Section: Better Faster More Efficient – How An Innovative Morphologmentioning
confidence: 98%